Using New Technologies to Promote Weight Management - Jane, Monica (Curtin University, 2017)
A clinical trial was conducted to determine whether incorporating social media into a weight management program would assist overweight and obese participants to achieve greater improvements in weight loss and metabolic syndrome risk factors than following the same program in written form alone. Psychological and behavioural outcome measures were also examined to elucidate the particular aspects of social media that assist participants to achieve the greater improvements in weight loss and other outcome measures.